3D Bioprinting of complex channels—Effects of material, orientation, geometry, and cell embedding. Issue 8 (28th December 2014) - Wüst, Silke; Müller, Ralph; Hofmann, Sandra
Abstract Creating filled or hollow channels within 3D tissues has become increasingly important in tissue engineering. Channels can serve as vasculature enhancing medium perfusion or as conduits for nerve regeneration. The 3D biofabrication seems to be a promising method to generate these structures within 3D constructs layer‐by‐layer. In this study, geometry and interface of bioprinted channels were investigated with micro‐computed tomography and fluorescent imaging. In filament printing, size and shape of printed channels are influenced by their orientation, which was analyzed by printing horizontally and vertically aligned channels, and by the ink, which was evaluated by comparing channels printed with an alginate‐gelatin hydrogel or with an emulsion. The influence of geometry and cell‐embedding in the hydrogel on feature size and shape was investigated by printing more complex channels. The generation of hollow channels, induced through leaching of a support phase, was monitored over time. Horizontally aligned channels provided 16× smaller cross‐sectional areas than channels in vertical orientation. The smallest feature size of hydrogel filaments was twice as large compared to emulsion filaments. Feature size and shape depended on the geometry but did not alter when living cells were embedded. With that knowledge, channels can be consciously tailored to the particular needs. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 2558–2570, 2015.